Measuring the impact of suppression on visual acuity in children with amblyopia using a dichoptic visual acuity chart - Zhu, Bixia; Liao, Meng; Liu, Longqian (Frontiers in Neuroscience, 2022)
Purpose: To develop a novel dichoptic visual acuity chart that measures the impact of interocular suppression on the visual acuity of each eye when two eyes are open. Methods: Fifty-four subjects (19 anisometropic amblyopia, 20 treated amblyopia and 15 normal children) participated in this study. The visual acuity tested under dichoptic-optotypes condition (i.e., presented optotypes to the untested eye) was compared with that under monocular condition (i.e., cover the untested eye with opaque patch). Visual acuity differences between these two conditions were compared among the three groups. The correlations between visual acuity differences and the depth of interocular suppression were then computed. Some participants performed the visual acuity test under dichoptic-luminance condition (i.e., presented mean luminance to the untested eye), and the test-retest reliability was established. Results: Reduced visual acuity of the non-dominant eye was found in the dichoptic-optotypes condition for the amblyopia group (P < 0.001) and the treated group (P = 0.001); the difference in the treated group was less than that in the amblyopia group (P < 0.001) but more than that in the normal group (P = 0.026). A significant correlation was found between the visual acuity differences and the depth of suppression, which was tested with a binocular phase combination task (P = 0.005). No change was found in the dichoptic-luminance condition. Conclusions: The amblyopic eye and the previous amblyopic eye seem to suffer from reduced visual acuity when two eyes are open due to suppression. This was successfully captured using our reliable dichoptic-optotypes visual acuity chart.